Anonymous

# PLEASE HELPPP!!!!!!?

If f(x)=4(^3-2x) , determine the value of:

f(2+x)f(2-x)

### 3 Answers

Relevance

- Engr. RonaldLv 71 month ago
f(2 + x)f(2 - x)

= 4^[3 - 2(2 + x)]*4^[3-2(2 - x)]

= 4^[3 - 4 - 2x] * 4^[3 - 4 + 2x]

=4^(-1 - 2x) * 4^(-1 + 2x)

=4^[ - 1 - 2x - 1 + 2x)

=4^-2

=1/4^2

=1/16 Answer//

- Log in to reply to the answers

- ?Lv 71 month ago
// There's a typo in your equation: f(x)=4(^3-2x)

// Assuming you mean f(x) = 4³⁻²ˣ then

f(x) = 4³⁻²ˣ

f(2+x) = 4³⁻²⁽²⁺ˣ⁾ = 4⁻¹⁻²ˣ

f(2-x) = 4³⁻²⁽²⁻ˣ⁾ = 4⁻¹⁺²ˣ

So,

f(2+x) f(2-x) = 4⁻¹⁻²ˣ 4⁻¹⁺²ˣ = 4⁻² = ¹⁄₁₆...............ANS

- Log in to reply to the answers

- AshLv 71 month ago
f(x) = 4^(3-2x)

f(2+x) = 4^(3 - 2(2+x)) = 4^(3-4-2x) = 4^(-1-2x)

f(2-x) = 4^(3 - 2(2-x)) = 4^(3-4+2x) = 4^(-1+2x)

f(2+x)f(2-x) = [4^(-1-2x)][4^(-1+2x)] = 4^(-1-2x+(-1+2x)) = 4⁻² = 1/16

- Log in to reply to the answers

Still have questions? Get answers by asking now.